Invasion of two Labidesthes species through the Tennessee-Tombigbee Waterway in Mississippi - Benjamin H. Chaffins; Calvin R. Rezac; Robert J. Ellwanger (Southeastern Fishes Council Proceedings, 2022)
We re-identified the collections of Labidesthes sicculus at Mississippi Museum of Natural Science after a 2015 publication by Werneke and Armbruster elevated Labidesthes vanhyningi to the full species level. Following re-examination of specimens, 64% were identified as L. vanhyningi and 36% were identified as L. sicculus. During our study, a chronological review of the distribution of both species suggested bi-directional invasion through the Tennessee-Tombigbee Waterway. Prior to the connection of the two drainages, the only Labidesthes located in the Tennessee drainage was L. sicculus, where as L. vanhyningi was allopatric within the Tombigbee drainage. However, following canal construction, we noted 34 collections of L. sicculus in the Tombigbee drainage and two collections of L. vanhyningi in the Tennessee drainage. Our findings are consistent with previous studies that have noted silverside species utilizing canal construction to expand their range. Our study adds to the growing literature on the impacts of natural stream channel alteration on native fish communities and documents the importance of natural science collections.
Keywords: Stream Alteration; Museum Collections; Taxonomy; Fish Distribution